Innovative Strategies for Learning Islamic Religious Education for Children with Special Needs: A Systematic Literature Review - Ely Fitriani; Desi Ariyani; Nur Kholis; Hanun Asrohah; Erfin Walida Rahmania; Machfud Bachtiyar (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Islamic Religious Education (IRE) for children with special needs requires innovative and adaptive learning strategies to accommodate the diversity of characteristics and special needs of students. This study aims to describe the distribution and main findings of articles on PAI learning strategies for children with special needs from 2019 to 2024, identify emerging patterns of innovation, and examine strategies that have been proven effective based on empirical evidence. Using the systematic literature review (SLR) method with the PRISMA guidelines, this study analysed 42 selected journal articles from 200 initial publications through the Google Scholar database using the Publish or Perish 8 application. Four key findings were identified, including adjustments to learning aspects, the central role of teachers, the dynamics of supporting and inhibiting factors, and positive impacts on children with special needs. The innovation pattern led to three integrated dimensions: structural, pedagogical, and cultural-communal. The study's implications emphasise reforming a curriculum based on Universal Design for Learning, strengthening teacher training, and providing inclusive technological infrastructure. Further research is recommended to examine the comparative effectiveness of strategies, develop authentic assessment instruments, investigate long-term impacts, and explore artificial intelligence in PAI learning for children with special needs.